2018
DOI: 10.3389/fmicb.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP Regulates Various Phenotypes and Insecticidal Activity of Gram-Positive Bacillus thuringiensis

Abstract: C-di-GMP has been well investigated to play significant roles in the physiology of many Gram-negative bacteria. However, its effect on Gram-positive bacteria is less known. In order to more understand the c-di-GMP functions in Gram-positive bacteria, we have carried out a detailed study on the c-di-GMP-metabolizing enzymes and their physiological functions in Bacillus thuringiensis, a Gram-positive entomopathogenic bacterium that has been applied as an insecticide successfully. We performed a systematic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 108 publications
(156 reference statements)
3
24
0
Order By: Relevance
“…2A). Consistent with our previous RNA-seq data (Fu et al, 2018), we found that the TSS is 72 bp upstream of the start codon of the open reading frame of prpC. We further identified the −10 and −35 promoter regions of the prp operon according to the established TSS ( Fig.…”
Section: Ccpa and Abrb Repress Transcription Of The Prp Operonsupporting
confidence: 90%
See 1 more Smart Citation
“…2A). Consistent with our previous RNA-seq data (Fu et al, 2018), we found that the TSS is 72 bp upstream of the start codon of the open reading frame of prpC. We further identified the −10 and −35 promoter regions of the prp operon according to the established TSS ( Fig.…”
Section: Ccpa and Abrb Repress Transcription Of The Prp Operonsupporting
confidence: 90%
“…The RNA integrity value (RIN) was then measured using an RNA 6000 Pico LabChip of Agilent 2100 Bioanalyzer (Agilent, Santa Clara, CA, USA). Removal of rRNA, construction of cDNA libraries and Illumina Sequencing were carried out as described (Su et al, 2016;Li et al, 2017;Fu et al, 2018).…”
Section: Rna Isolation and Quantitative Transcriptomics (Rna-seq)mentioning
confidence: 99%
“…For the extraction of the ICPs, the strains were grown under the GYS medium for 20 h, when cells started to lyse, 20 mL of each culture was separately collected. The procedures for extracting ICPs were performed according to previous studies (Wang X. et al, 2016; He et al, 2018). Finally, the ICPs were visualized by SDS-PAGE, and the ICPs concentrations were measured by the Bradford method.…”
Section: Methodsmentioning
confidence: 99%
“…The total sample volumes of 15 mL each from BMB171 and its derivative strains cultured in either the TSB, TSB-Na for 6 h or GYS for 11 h were centrifuged, with cell pellets ground in liquid nitrogen. Total RNA was isolated, and RT-qPCR was performed as described previously 33,56,57 . In those experiments, either the gapdh or 16S rRNA gene was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%